Collaborative mining using different equipment for a coal seam varying in thickness in a long wall working face. (2016) - Chen, Shaojie; Yin, Dawei; Liu, Xiaoyan; Wang, Hailong; Pu, Zhiqiang
Efficient mining of coal seams varying in thickness has become increasingly important, especially for the coal resources located at the edges of coal seams, in corners or panels. Selecting the 4320 mechanised working face in the Daizhuang Coal Mine located in eastern China as example, collaborative mining technology with different mining equipment for a coal seam varying in thickness within the same long wall working face was studied. A number of key technologies were developed, including scraper conveyor lap technology, a separation device for coal and gangue and working face shortening technology. The roof movement formula for this working face was also monitored. The engineering application showed that this technology could greatly improve the degree of mechanisation, and reduce the labour intensity of workers. Besides, more than 8.3 Mt of coal were recovered. The results of monitoring the roof movement indicated that stress concentration was located at the junction of thin and thick coal seams, but it did not appear to affect normal operations within the coal mine, and the periodic pressure in this working face was steady. The above achievements could provide technical reference for coal mining under similar geological conditions in other locations. [Received: December 4, 2014; Accepted: September 20, 2015]